2019
DOI: 10.3390/educsci9030189
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Expectations of International Students at Historically Black Colleges and Universities: An Interpretative Phenomenological Analysis

Abstract: International students are the most important population in the American higher education system, particularly for students from different cultural backgrounds. Besides research-based universities, comprehensive universities, and liberal arts colleges, historically black colleges and universities have the traditions to provide an equal learning environment to minorities, including international students. This study aimed to understand the academic experiences and expectations of Chinese international students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…In fact, the eating habits of East Asian American people and local American people is totally different due to cultural differences. Some previous studies indicated that international personnel might have cultural conflicts in hosted countries due to misunderstanding and cultural differences [ 46 , 54 , 55 , 56 ]. Therefore, when western teachers instruct Asian people’s eating habits, the cultural differences and misunderstanding may increase conflicts between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the eating habits of East Asian American people and local American people is totally different due to cultural differences. Some previous studies indicated that international personnel might have cultural conflicts in hosted countries due to misunderstanding and cultural differences [ 46 , 54 , 55 , 56 ]. Therefore, when western teachers instruct Asian people’s eating habits, the cultural differences and misunderstanding may increase conflicts between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…As an established qualitative researcher [ 26 , 27 , 28 , 35 , 36 , 37 , 38 , 39 ] in the field of public health, education, nursing, and social sciences, the researcher decided to employ a qualitative research method to collect and analyse the data information into meaningful themes and subthemes for reporting. The nature of this study is to understand and explore the lived stories, shared information, life experiences, sense of belonging, and decision-making processes [ 33 , 40 , 41 , 42 , 43 , 44 ] of nursing students during the COVID-19 pandemic in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…The open-ended and semi-structured interview tools [ 38 , 39 , 46 ] were employed to collect meaningful data and information from the participants. The individuals shared their understanding, life experiences, sense of belonging, decision-making processes, and feedback as Japanese nursing students [ 33 , 40 , 41 , 42 , 43 , 44 ] and how the COVID-19 pandemic influenced their behaviours. All participants have voluntarily participated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Two types of tools were employed, including individual and focus group activities [40,43,45]. The individual interviews were conducted to explore their understanding, life experience, and family issues under a private sharing environment [46][47][48]. The focus group activities were conducted to explore some similar background, social and family expectations, social bias, and interests.…”
Section: Data Collectionmentioning
confidence: 99%